Pengaruh Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada Badan Kesbangpol Kota Tangerang - Hamjah, Robiy Saepul; Sutisna, Eka; Faisal, Muhammad Gelar (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to determine the influence of work discipline and job satisfaction on employee performance at the Tangerang City Kesbangpol Agency. This type of research uses quantitative methods. In this research, primary data was used in the form of a questionnaire to 40 Kesbangpol Tangerang City employees. The data analysis technique uses inferential analysis with multiple linear regression and hypothesis testing using the Statistical Product and Security Solution (SPSS) version 29.0 program. Based on the results of the tests carried out, it shows that simultaneously Work Discipline and Job Satisfaction have a positive and significant effect on the performance of Tangerang City Kesbangpol Agency employees. Meanwhile, partially Work Discipline has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. The results of this research hope that companies can improve work discipline and job satisfaction which can support employee performance.